Use of vasoactive drugs in the management of shock: a literature review (Research, Society and Development, 2022)
Acute diseases are often characterized by alterations in cardiovascular homeostasis. Underlying mechanisms may include multiple factors that alter blood volume (actual or effective), cardiac function (diastolic and/or systolic), or vessels (large vessels and/or microvasculature). The present study aims to analyze which vasoactive drugs are used in the management of shock. This is a study with a qualitative approach, where the integrative literature review was adopted, which according to Galvão (2012), is a construction of a broad analysis of the literature with pre-defined steps. Conducted through the Virtual Health Library (BVS) in the Pubmed databases, using the crossings of the English descriptors “Vasoactive Drug”, “Catecholamines”. Vasoactive agents are classified into sympathomimetics, vasopressin analogues and angiotensin II. Catecholamines are subdivided into indirect-acting, mixed-acting, and direct-acting categories. Only direct action agents have a role in the shock. Direct agents are further delineated by their selective nature (eg, dobutamine, phenylephrine) or non-selective activity (eg, epinephrine, norepinephrine) at α1, α2, β1, β2, and β3 receptors. Catecholamines are most often associated with clinical improvement in shock states. Vasoactive drugs are part of the treatment of shock and must be chosen according to the patient's need, so it is essential that health professionals have adequate knowledge of these drugs to better serve each case.